Osteoblast‐specific expression of the fibrous dysplasia (FD)–causing mutation GsαR201C produces a high bone mass phenotype but does not reproduce FD in the mouse. (June 2015) - Remoli, Cristina; Michienzi, Stefano; Sacchetti, Benedetto; Consiglio, Alberto Di; Cersosimo, Stefania; Spica, Emanuela; Robey, Pamela G; Holmbeck, Kenn; Cumano, Ana; Boyde, Alan; Davis, Graham; Saggio, Isabella; et al.
ABSTRACT We recently reported the generation and initial characterization of the first direct model of human fibrous dysplasia (FD; OMIM #174800), obtained through the constitutive systemic expression of one of the disease‐causing mutations, GsαR201C, in the mouse. To define the specific pathogenetic role(s) of individual cell types within the stromal/osteogenic system in FD, we generated mice expressing GsαR201C selectively in mature osteoblasts using the 2.3kb Col1a1 promoter. We show here that this results in a striking high bone mass phenotype but not in a mimicry of human FD. The high bone mass phenotype involves specifically a deforming excess of cortical bone and prolonged and ectopic cortical bone remodeling. Expression of genes characteristic of late stages of bone cell differentiation/maturation is profoundly altered as a result of expression of GsαR201C in osteoblasts, and expression of the Wnt inhibitor Sost is reduced. Although high bone mass is, in fact, a feature of some types/stages of FD lesions in humans, it is marrow fibrosis, localized loss of adipocytes and hematopoietic tissue, osteomalacia, and osteolytic changes that together represent the characteristic pathological profile of FD, as well as the sources of specific morbidity. None of these features are reproduced in mice with osteoblast‐specific expression of GsαR201C. We further show that hematopoietic progenitor/stem cells, as well as more mature cell compartments, and adipocyte development are normal in these mice. These data demonstrate that effects of Gsα mutations underpinning FD‐defining tissue changes and morbidity do not reflect the effects of the mutations on osteoblasts proper. © 2015 American Society for Bone and Mineral Research. © 2014 American Society for Bone and Mineral Research